Avaliação do pico pré-ovulatório de LH em ovelhas da raça Santa Inês superestimuladas nos períodos de ciclicidade, transição e anestro - Rossi, Carla Cristina D'Amato [UNESP] (2012)
In the protocols of multiple ovulation and embryo transfer (MOET) various treatments have been tested in order to increase the efficiency of biotech, including those aimed at overstimulation started next to follicular waves of emergencies. However, these cause endocrine ovarian and modifications as LH surge. Knowing the time of estrus, LH surge and ovulation, are essential to ensure the advancement and efficiency of biotech reproduction. The timing and amplitude of the pre-ovulatory LH surge has been one of the best parameters to predict the time of ovulation. According to this problem the present study aimed to investigate the onset of estrus, the timing and extent of the pre-ovulatory LH surge in sheep subjected to superovulation treatments with FSH, started near the emergence of the first and last follicular waves during the periods of cyclicity , transition and anoestrus. For this we used two hormonal protocols to overstimulation of the first wave and three protocols for last follicular wave in different periods, namely, anestrus, transition and cyclicality. All animals received an intravaginal device and administration of D-cloprostenol on D0. The application FSHp eight decreasing doses started 48 hours before removal of the intravaginal device and applications associated with eCG D-cloprostenol. The blood collection for LH dosage occurred every three hours and were measured by radioimmunoassay, and there was the time and amplitude of the pre-ovulatory LH surge. The results showed that the best treatment is to be performed follicular overstimulation of the first wave at the time of cyclicity, which obtained the highest amplitude of the pre-ovulatory LH surge and ovulation rates best. Keyword: overstimulation, hormonal protocols; LH peak; Sheep